329 An Integrated Care Approach to the Uses of Social Prescribing in an Acutely Frail Older Adult Cohort. (16th September 2019) - McLoughlin, Petra; Murphy, Eleanor; O'Sullivan, Fiona; Connellan, Ciara
Abstract: Background: Community Health Organisation Area 1 has the highest age dependency in Ireland (37.5 vs 34.5) and the highest proportion of its population engaged in unpaid care (4.7%) 1 . Social prescribing is a novel tool used by the Integrated Care Team for the Older Person in Sligo to address social determinants of health such as social isolation and to minimise the impact of carer burden. The study aim is to quantify social needs and carer burden in this acutely frail group and describe interventions to address this. Methods: A descriptive study compiled from Comprehensive Geriatric Assessment of patient care profile and social prescribing from June to December 2018. Results: 50% of patients studied did not have a supportive, able person living with them. 1 in 4 had no local support while 1 in 5 were supported only by neighbours or friends. 53% were not receipt of home help while 24% paid for private care or cleaning services. Carer burden was reported in half of cases with a 2.2 times increased risk with a patient co-morbidity of cognitive decline and a 1.8 times increased risk with a complex medical needs patient. Intervention increased community service usage such as the public health nurse from 70% to 86% and home help applications by 26%. Social prescribing increased day centre use from 18% to 46% and Meals on Wheels usage by 50%. Dementia specific social prescribing was made in 26% of those with cognitive difficulties. 33% received information for carers while 11% were informed of respite options. Conclusion: In this acutely decompensated and vulnerable group social isolation and carer burden are a significant issue. Our study indicates the potential for the use of a social prescribing model to address this at an earlier point in frailty development at a primary care level.